Text linguistics (discourse analysis); grammar of the text (textual grammar), transphrase grammar and transsentential grammar - Miranda, Luis (2014)
This article discusses a few words that have been used in language-related sciences lately, due mostly to the expansion of language studies toward units larger than the sentence, and to the consideration of speaking circumstances.